Evaluating User Readiness for IoT-Based Smart Home Adoption: A PLS-SEM and IPMA Study Integrating TAM and Technological Readiness Model in the Context of NTB, Indonesia - Wire Bagye; Khairul Imtihan; Maulana Ashari (Depart. of Information Systems, FST, UIN Syarif Hidayatullah Jakarta, 2025)
The swift evolution of Internet of Things (IoT) innovations has significantly accelerated the integration of smart home solutions into everyday life. However, user readiness remains a pivotal aspect for ensuring successful adoption, particularly in developing regions such as Indonesia. This study aimed to evaluate user readiness for IoT-based smart home adoption by integrating the Technology Acceptance Model (TAM) and the Technology Readiness Index (TRI) within the socio-cultural context of Nusa Tenggara Barat (NTB) province, Indonesia. A quantitative survey involving 496 respondents was conducted using purposive sampling during the 2025 data collection period. The data were analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM) and Importance-Performance Map Analysis (IPMA). The results indicate that optimism, innovativeness, and digital literacy have a significant influence on perceived ease of use and perceived usefulness. In contrast, discomfort and insecurity negatively affect user acceptance. Furthermore, perceived ease of use and perceived usefulness were found to predict behavioral intention strongly. The IPMA results further highlight optimism and innovativeness as high-impact yet underperforming areas that require attention. This study contributes theoretically by extending the integration of TAM and TRI in the context of IoT-based smart home adoption, while providing practical insights for policymakers, system designers, and digital transformation stakeholders to design more inclusive and user-aligned smart home strategies. The combined TAM–TRI framework reflects both cognitive and emotional elements that shape user decision-making, thereby strengthening the understanding of technology adoption in developing regions.